Regional Fiscal Policy and The Phenomenon of Poverty in Indonesia - Yesi Aprianti; Hotsawadi; Emmilya Umma Azizah Gaffar; Muliati (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2025)
The poor population in Indonesia is unevenly distributed across districts and cities. This research aims to measure the impact of regional fiscal policy on reducing poverty levels. Regional financial transfers (TKD) serve as an instrument for central government intervention. The study also focuses on the classification of regional government spending and its relationship to poverty levels. Data were collected from 2016 to 2022 across Indonesian districts and cities, excluding regions with divergent data trends. The hypothesis posits that the impact of expenditure allocation across sectors varies in its effectiveness in alleviating poverty. To test this, the study employs a panel ARDL analysis to capture potential lag effects in the predictors. The main finding reveals the consistent influence of regional income on poverty reduction in both the short and long term. Meanwhile, TKD has a positive impact, as part of its fiscal gap component targets assistance to areas with high poverty levels. However, regional spending from various sources also shows a positive correlation with poverty rates, although with relatively low coefficient values. This suggests that poverty reduction is not yet a central focus of regional government spending